Regional Integration in South Asia (Based on SAARC) - Iyer, Arun; Druláková, Radka, 1973-; Maslowski, Nicolas, 1972-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The aim of the thesis was to show the weakness of SAARC right from its origins as well as a great flaw in the making of the charter which excluded the notion of security as well as "bilateral" and "contentious" issues to be discussed in the organization. South Asia has for long been an area prone to violence and mistrust and the exclusion of elements of vital importance has further added to the weakness of SAARC. In the following work I will portray the dynamics and working of the region of SAARC as well as individual countries on how it affects the region as a whole and also why SAARC continues to be a toothless organization in-spite knowing the origin of the problem and why nothing is being done. Also, with the case study of India and Pakistan, it shows us that when two nations of totally opposite ideologies and bloody beginnings since independence exist within the region, the idea of integration is a far fetched dream.
Vedoucí práce: Radka Druláková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses